Konstruksi Realitas Feminisme Liberal dalam Film Barbie (2023) Karya Greta Gerwig - Fera Meilia Ananda Putri; Masnia Ningsih; Ratnaningrum Zusyana Dewi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Movies always construct how reality happens in the real world, many things can be constructed and discussed in a film, one of which is about liberal feminism, liberal feminism is a view to place women to have full and individual freedom. This research will discuss how the construction of liberal feminism reality in the Barbie (2023) movie by Greta Gerwig. The purpose of this study is to find out how the construction of liberal feminism reality is depicted in the Barbie (2023) movie by Greta Gerwig. The research method used in this study is a qualitative research method using a content analysis approach. By referring to the theory of liberal feminism, this study produces a conclusion about the existence of a scene about liberal feminism, precisely about the freedom of women to do anything in their lives such as the freedom to achieve dreams, the freedom to be a leader, the freedom to do good, the freedom to fight oppression, the freedom to get happiness, and the freedom to receive awards which are part of the construction of the reality of the world today. The construction of reality appears in a Barbie movie because the director of this Barbie movie wants to show how the state of the world now often makes all women feel threatened and not free to do anything according to their wishes, besides that through this movie the director of the movie wants that there will be no more injustice or unfreedom for women. The implications that occur here can certainly make the audience who has watched this movie can treat anyone, especially women, well, namely giving justice and freedom wherever they are and the audience can understand that the movie is created from the existing reality, then neatly constructed into a movie by presenting a moral message that is useful for anyone.